Considering DNA damage when interpreting mtDNA heteroplasmy in deep sequencing data. (January 2017) - Rathbun, Molly M.; McElhoe, Jennifer A.; Parson, Walther; Holland, Mitchell M.
Highlights: Miscoding lesions accumulate as storage condition and targeted DNA damage worsens. The majority of miscoding lesions have a 1–2% minor variant frequency. Miscoding lesions are typically not replicated from the same DNA extract. Miscoding lesions reduce the mtDNA heteroplasmy transition:transversion ratio. Sequences with DNA damage may require modified heteroplasmy reporting thresholds. Abstract: Resolution of mitochondrial (mt) DNA heteroplasmy is now possible when applying a massively parallel sequencing (MPS) approach, including minor components down to 1%. However, reporting thresholds and interpretation criteria will need to be established for calling heteroplasmic variants that address a number of important topics, one of which is DNA damage. We assessed the impact of increasing amounts of DNA damage on the interpretation of minor component sequence variants in the mtDNA control region, including low-level mixed sites. A passive approach was used to evaluate the impact of storage conditions, and an active approach was employed to accelerate the process of hydrolytic damage (for example, replication errors associated with depurination events). The patterns of damage were compared and assessed in relation to damage typically encountered in poor quality samples. As expected, the number of miscoding lesions increased as conditions worsened. Single nucleotide polymorphisms (SNPs) associated with miscoding lesions were indistinguishable from innate heteroplasmy and were most often observed as 1–2% of the total sequencing reads. Numerous examples of miscoding lesions above 2% were identified, including two complete changes in the nucleotide sequence, presenting a challenge when assessing the placement of reporting thresholds for heteroplasmy. To mitigate the impact, replication of miscoding lesions was not observed in stored samples, and was rarely seen in data associated with accelerated hydrolysis. In addition, a significant decrease in the expected transition:transversion ratio was observed, providing a useful tool for predicting the presence of damage-induced lesions. The results of this study directly impact MPS analysis of minor sequence variants from poorly preserved DNA extracts, and when biological samples have been exposed to agents that induce DNA damage. These findings are particularly relevant to clinical and forensic investigations.